'Manobras no Porto' project (Porto): What can creative activism do for policies and urban place(-making) and the other way around. (March 2017) - Romeiro, Patricia
Abstract: In recent decades, much has been written about urban policies for culture and creativity. Little is known, however, about how public policies are shaped in practice at local level. To what extent are the different notions and forms of creativity activated and mobilized, and contribute to the development of urban policies for culture and creativity? Recent literature on urban studies drew attention to the creative activism practices contesting the instrumentalisation of culture and creativity by neo-liberal approaches to urban development. Recognizing the potential of creative activism as a creative practice of critical reflection and action, this paper focuses on an underexplored perspective so far – creative activism developed in dialogue and cooperation, and not as a practice of radical opposition, and oriented to have impacts beyond the temporality of the actions developed. Through the analysis of a case study – Manobras no Porto (Porto, Portugal), we explore how a creative activism project can be understood as a space for the experimentation of new spaces of governance. The results show not only that creative activism can play an important role in policy learning and urban place-making, but that policies and place (as context and content) can also have a decisive effect on the activation of creative activism practices. Highlights: Creative activism can be developed in dialogue and cooperation. Creative activism can play an important role in policy learning and in place-making. Creative policies and place can also have a decisive effect on creative activism.